Radical resection versus local excision for low rectal gastrointestinal stromal tumor: A multicenter propensity score-matched analysis. Issue 7 (July 2021) - Wang, Tao; Zhao, Yan; Wang, Ming; Zhang, Peng; Lin, Guole; Liu, Qian; Feng, Fan; Xiong, Zhiguo; Hu, Junbo; Zhang, Bo; Ye, Yingjiang; Xia, Lijian; et al.
Abstract: Background: The surgical approaches and resection extent for rectal gastrointestinal stromal tumors (GISTs) are controversial due to the low incidence of this disease. A multicenter retrospective cohort study was conducted to compare the postoperative and oncologic outcomes of local excision (LE) and radical resection (RR) in patients with low rectal GIST. Patients and methods: The medical records of rectal GIST patients from 11 large-scale medical centers in China (January 2000-December 2019) were reviewed. All patients were divided into either the LE group or the RR group. Propensity score matching (PSM) was conducted to reduce confounders. Results: A total of 280 patients with low rectal GIST were enrolled. After PSM, 144 patients were included (72 in each group). The LE group showed a higher anal preservation rate (100.0% vs. 76.4%, P  < 0.001), shorter operation time (77.1 ± 68.4 min vs. 159.1 ± 83.6 min, P  < 0.001), fewer complications (8.3% vs. 22.2%, P  = 0.021) and shorter postoperative hospital stay (4.9 ± 4.1 d vs. 10.7 ± 8.1 d, P  < 0.001) than the RR group. There was no significant difference in recurrence-free survival (RFS) between the RR and LE groups among patients with tumors ≤2 cm ( P  = 0.220), and the RR group had a superior RFS than the LE group in patients with tumors >2 cm ( P  = 0.046). Conclusions: LE resulted in improved postoperative outcomes and comparable oncological safety with a low rectal GIST of ≤2 cm. However, for patients with a low rectal GIST of >2 cm, RR might be a more appropriate option with better RFS.